Obtenção do índice de esforço fiscal na arrecadação do IPTU dos municípios do Ceará de 2008 a 2016 utilizando o modelo de fronteira estocástica - Martins, Vanessa Souza (2019)
This article aimed to make an analysis on the collection of the Urban Property Tax (IPTU) of the municipalities of the State of Ceará from 2008 to 2016. Specifically, it aimed to show the fiscal performance of the municipalities of Ceará in the collection of property tax / per through the fiscal effort index, calculated using the stochastic frontier methodology. A database was used for the 184 municipalities of Ceará from 2008 to 2016, and the main sources were: from the Court of Auditors of the State of Ceará, through the Municipal Information System (SIM) database, and the Brazilian Institute of Geography and Statistics - IBGE. The results indicated that during the municipal election period the IPTU \ per capita collection is influenced, the same was observed with the variables: FPM (Municipal Participation Fund) and GDP (Gross Domestic Product), both are related to the collection. IPTU \ per capita of the municipalities of Ceará. The results indicated that municipalities most efficient in collecting IPTU / per capita did not exceed 50% in the collection of IPTU / per capita.